Antisperm antibodies in infertile men and their correlation with seminal parameters - Garcia, Patricia C. [UNESP]; Rubio, Eliana M. [UNESP]; Pereira, Oduvaldo Cämara Marques [UNESP] (Wiley, 2007)
Aim: Antisperm antibodies (ASA) in males cause the autoimmune disease 'immune infertility'. The present study intended to detect the presence of ASA and their incidence in men with unexplained infertility, as well as to evaluate the correlation between the presence of ASA and semen parameter alterations. Methods: Blood and sperm assessment were collected to carry out a direct and indirect mixed antiglobulin reaction (MAR) test and semen analysis in infertile and fertile men from the University Hospital of the Faculty of Medicine, Sao Paulo State University, Sao Paulo. Results: In the MARtest, 18.18% of infertile men were positive for ASA. In fertile men, no positivity was found. A significant correlation between the presence of ASA with an increased white blood cell count plus a decreased hypoosmotic swelling test result was observed. Conclusions: The results indicate that ASA are involved in reduced fertility. It is not ASA detection per.se that provides conclusive information about the occurrence of damage to fertility. The correlation between infertility and altered seminal parameters reinforce the ASA participation in this pathology. © 2007 The Authors Journal compilation. © 2007 Japan Society for Reproductive Medicine.
Keywords: Antisperm antibody; Infertility; Man; Semen; Seminal parameters; immunoglobulin antibody; sperm antibody; adult; antibody detection; blood analysis; Brazil; controlled study; correlation analysis; human; human cell; incidence; leukocyte count; major clinical study; male; male infertility; osmosis; pathophysiology; priority journal; semen analysis; spermatozoon count; spermatozoon motility